Developing Entrepreneurial Spirit of Young Generation through Business Plan Training - Dwi Hasmidyani; Siti Fatimah; Firmansyah Firmansyah (Institute for Research and Community Services, 2017)
The potential of developing and fostering the entrepreneurial spirit of the young generation in RW 11 Sukarami Palembang urban village was enormous, but the fostering of entrepreneurship spirit had not been optimal yet because the education level of most target audiences was high school graduates who lacked knowledge in entrepreneurship. As a result, many potential creative ideas in starting a business had not been explored optimally. The aim of this business planning training was expected to instill the entrepreneurial spirit into this young generation. It is hoped that they were motivated to start their own businesses that suit their own talents or hobbies and they were able to utilize existing resources and capital to create economic value goods. Several different methods were used in the training such as lecture, game, discussion, question and answer, and business planning practice. During the training, the participants were invited to present their business plans. The results of the evaluation of 22 trainees, in general, show that there was an increase of knowledge and understanding after the participants had been exposed to the materials of entrepreneurship and business planning.